20. MELANOMA CELL INTRINSIC GABAA RECEPTOR ENHANCEMENT POTENTIATES RADIATION AND IMMUNE CHECKPOINT INHIBITOR RESPONSE BY PROMOTING DIRECT AND T CELL-MEDIATED ANTI-TUMOR ACTIVITY. (4th August 2020) - Sengupta, Soma; Nasti, Tahseen; Kaluzova, Milota; Kallay, Laura; Melms, Johannes; Izar, Benjamin; Xu, Maxwell; Bhattacharya, Debanjan; Burnham, Andre; Li, Guanguan; Ahmed, Taukir; Lawson, David; et al.
Abstract: Most metastatic melanoma patients exhibit poor and variable response to radiotherapy and targeted therapies, including immune checkpoint inhibitors. There is a need for therapeutics that can potentiate existing treatments to positively impact clinical outcomes of metastatic melanoma patients. We reanalyzed melanoma TCGA transcriptomes and identified, as linked to previously defined molecular subgroups, enhanced expression of genes coding for subunits of the Type A GABA receptor (GABAA R), a chloride ion channel and major inhibitory neurotransmitter receptor. Using whole-cell patch clamp electrophysiology, we find that melanoma cells possess GABAA Rs that control membrane permeability to anions. Select benzodiazepines, by enhancing GABAA R mediated anion transport, depolarize melanoma cell mitochondrial membrane potential and impair cell viability in vitro . Using a syngeneic melanoma mouse model, we find that a benzodiazepine promotes reduction in tumor volume when administered alone and potentiated radiation or immune checkpoint inhibitor α-PD-L1. When a benzodiazepine is combined with concurrent α-PD-L1 and a sub-lethal radiation dose, there is near complete loss of tumor, beyond what is observed for benzodiazepine with radiation or α-PD-L1. Mechanistically, benzodiazepine with radiation or α-PD-L1 results in ipsilateral and an abscopal tumor volume reduction commensurate with enhanced infiltration into the tumor milieu of polyfunctional CD8 T-cells. There is also an increased expression of genes with roles in the cytokine-cytokine receptor and p53 signaling pathways. This study provides evidence for melanoma cell GABAA Rs as a therapeutic vulnerability with benzodiazepines promoting both direct and immune-mediated anti-tumor activity.